Predicting transient ischemic attack risk in patients with mild carotid stenosis using machine learning and CT radiomics - Xia, Hai; Yuan, Lei; Zhao, Wei; Zhang, Chenglei; Zhao, Lingfeng; Hou, Jialin; Luan, Yancheng; Bi, Yuxin; Feng, Yaoyu (Frontiers in Neurology, 2023)
Abstract Objective: This study aims to establish a radiomics-based machine learning model that predicts the risk of transient ischemic attack in patients with mild carotid stenosis (30%–50% North American Symptomatic Carotid Endarterectomy Trial) using extracted Computed Tomography radiomics features and clinical information. Methods: 179 patients underwent carotid Computed Tomography Angiography. 219 carotid arteries with a plaque at the carotid bifurcation or proximal to the internal carotid artery were selected. The patients were divided into two groups; patients with symptoms of transient ischemic attack after CTA; and patients without symptoms of transient ischemic attack after CTA. Then we performed random sampling methods stratified by predictive outcome to obtain training set (N=180) and testing set (N=39). 3D Slicer was employed to select the site of plaque on the Computed Tomography image as the volume of interest. An open-source package PyRadiomics in Python was used to extract radiomics features from the volume of interests. The random forest and logistic regression models were used to screen feature variables, and five classification algorithms were used, including random forest, eXtreme Gradient Boosting, logistic regression, support vector machine and K-nearest neighbours. Data on radiomic feature information, clinical information, and the combination of these pieces of information was used to generate the model that predicts the risk of transient ischemic attack in patients with mild carotid artery stenosis (30%–50% North American Symptomatic Carotid Endarterectomy Trial). Results: The random forest model which was built based on the radiomics and clinical feature information has the highest accuracy (Area Under Curve=0.879; 95% Confidence Interval, 0.787-0.979). Combined model outperformed the clinical model, whereas the combined model showed no significant difference with the radiomics model. Conclusion: The random forest model constructed with both radiomics and clinical information can accurately predict and improve Computed Tomography Angiography's discriminative power in identifying ischemic symptoms in patients with carotid atherosclerosis. This model can aid in guiding the follow-up treatment of high-risk patients.